2019
DOI: 10.1002/app5.269
|View full text |Cite
|
Sign up to set email alerts
|

India's depleting groundwater: When science meets policy

Abstract: A commonly applied policy to India's ongoing depletion of groundwater is feeder separation. Introduced in Gujarat as the Jyotigram Yojana (JGY) scheme, it provides a separate and rationed electricity supply to farmers and an unrationed power supply to nonagricultural users. JGY is claimed to increase groundwater storage. By using Gujarat district-level data from 1996 to 2011 and by separately applying differencein-differences and Bayesian regressions, we find that groundwater storage has continued to decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Gujarat (Verma and Shah 2008), Punjab and Karnataka (Mukherji 2017) have undertaken feeder segregation and effectively rationed electricity supply for agricultural users. Some programs, like Gujarat's Jyotirgram Yojana (JGY) were initially deemed successful in improving electricity supply quality and reducing groundwater extraction (Verma and Shah 2008), although later studies found no long-term impacts on groundwater tables (Chindarkar and Grafton 2019). In Punjab, feeder segregation, and a host of other measures like high-voltage distribution systems, improved electricity-related outcomes, but those measures did not have any discernible impact on groundwater use because of the increasing number of electric wells in the state (Mukherji 2017).…”
Section: Electricity and Energy Initiatives Including The Current Foc...mentioning
confidence: 99%
“…Gujarat (Verma and Shah 2008), Punjab and Karnataka (Mukherji 2017) have undertaken feeder segregation and effectively rationed electricity supply for agricultural users. Some programs, like Gujarat's Jyotirgram Yojana (JGY) were initially deemed successful in improving electricity supply quality and reducing groundwater extraction (Verma and Shah 2008), although later studies found no long-term impacts on groundwater tables (Chindarkar and Grafton 2019). In Punjab, feeder segregation, and a host of other measures like high-voltage distribution systems, improved electricity-related outcomes, but those measures did not have any discernible impact on groundwater use because of the increasing number of electric wells in the state (Mukherji 2017).…”
Section: Electricity and Energy Initiatives Including The Current Foc...mentioning
confidence: 99%
“…The lack of access to water in such settings and community, might encumber its use and thereby adversely affect hygiene. The issues of ground water depletion and/or contamination could not be overstated for the adequate piped water supply in the rural India( Chindarkar & Grafton, 2019 ; Dinesh Kumar & Shah, 2010 ). When coming to the correlation between hygiene practices and the minimum quantity of water recommended, is always debatable.…”
mentioning
confidence: 99%
“…The difference might be due to the long-years over-withdrawal of groundwater for farming works that have co-operated the groundwater harvest volume at the current environmental situation in the river basin. Access to groundwater for agricultural use is also flattering progressively week to the dangers of groundwater reduction, which has been informed by numerous studies (Chindarkar et al 2019). To avoid groundwater depletion, modifying the conventional cropping types and implementing drips, sprinklers and micro-irrigation practices may be helpful for specific areas (Wang et al 2018;Kaarakka et al 2019).…”
Section: Validation Of Groundwater Potential Zone Mapsmentioning
confidence: 99%